The Effect Of Work Motivation And Work Environment On Employee Performance Through Job Satisfaction As A Mediating Variable at PT. PNM Depok - Nur Akmal; Sri Rahayu; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of Work Motivation and Work Environment on Employee Performance through Job Satisfaction as a mediating variable. The research employed a quantitative approach using a survey method involving 30 employees as respondents. A census sampling technique was applied, in which all members of the population were included as research respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS software. The measurement model evaluation demonstrated that all indicators satisfied the convergent validity criterion, with outer loading values exceeding 0.70. In addition, all constructs met the reliability requirements, with Cronbach's Alpha and Composite Reliability values greater than 0.70 and Average Variance Extracted (AVE) values above 0.50. The structural model results revealed that Work Motivation had a positive and significant effect on Job Satisfaction (β = 0.398), Work Environment positively and significantly influenced Job Satisfaction (β = 0.342), Work Motivation positively and significantly affected Employee Performance (β = 0.236), Work Environment positively and significantly affected Employee Performance (β = 0.287), and Job Satisfaction had the strongest positive and significant effect on Employee Performance (β = 0.401). Furthermore, Job Satisfaction was found to partially mediate the relationships between Work Motivation and Employee Performance, as well as between Work Environment and Employee Performance. The coefficient of determination indicated that the proposed model explained 52.1% of the variance in Job Satisfaction and 61.2% of the variance in Employee Performance. These findings suggest that improving employees' work motivation and creating a supportive work environment can enhance job satisfaction, which in turn contributes to better employee performance.